Aspects of 6-[18F]fluoro-L-DOPA preparation - Füchtner, F.; Zessin, J.; Mäding, P.; Wüst, F. (Nuklearmedizin - NuclearMedicine, 2008)
Aim: Replacement of the ecologically harmful solvent Freon 11 (CFCl3) by chloroform for the module-assisted preparation of 6-[18F]fluoro-L-DOPA based on the electrophilic radiofluorodestannylation of the precursor N-formyl- 3,4-di-tert-butoxycarbonyloxy-6-(trimethylstannyl)- L-phenylalanine ethyl ester. Materials, methods: The TRACERlab Fx FDOPA module (GE Medical Systems) was used for the preparation of 6-[18F]fluoro-L-DOPA. Cyclotron- produced [18F]F2 gas (5 GBq) was passed through a cooled solution (5°C) of the stannyl precursor (45 mg) in CDCl3 (10 ml). After the [18F]fluorination step, HCl (2 ml, 6 mol/l) was added to the solution. Then the reaction mixture was heated at 80°C for 5 min under vacuum to evaporate the chloroform. The hydrolysis to remove the protecting groups was completed by heating the closed reactor at 130°C for 8 min. After cooling to 20°C the reaction mixture was purified by HPLC with two polymer-based RP columns (PRP-1, 7 μm, 10 X 250 mm, Hamilton) using a solution of AcOH/AcONa (pH 4.7) as eluent. The 6-[18F]fluoro- L-DOPA fraction was collected and sterile filtrated. Results: Three types of stabilised chloroform were tested for the radiofluorination of the precursor. Only by use of deuterochloroform stabilised with silver no significant losses of radioactivity were observed. Thus, 6-[18F]fluoro-L-DOPA purified by HPLC was obtained in decay-corrected radiochemical yields of 25±3%, ready for human use. Conclusion: CDCl3 has proved to be a convenient solvent for the module-assisted preparation of 6-[18F]fluoro-L-DOPA. In this way the use of the polluting Freon 11 can be avoided.
Keywords: 6-[18F]fluoro-L-DOPA; electrophilic radiofluorodestannylation; Freon 11 substitution; deuterochloroform